Cryotherapy in sport: a warm reception for the translation of evidence into applied practice - Alexander, J.; Allan, R.; Rhodes, D. (Research in Sports Medicine, 2021)
Research contributing to the understanding of the mechanisms that underpin cryotherapy application in sport are evident. The translation of impactful findings that contribute to the design and implementation of cryotherapy protocols which are advantageous to the athlete in an applied sport setting, however, are still being explored. The role of cryotherapy for acute sport injury management is challenged in recent literature and discrepancies around the periodisation of cooling to maximise injury management or recovery, contribute to the confusion around optimal applications of cryotherapy in sport. The purpose of this work was to provide a contemporary summary of current perspectives, challenges and approaches for the use, application and translation of cryotherapy evidence into applied practice in a sporting context. The intention being to stimulate further debate on the topic and highlight key considerations for future study designs that reflect current practices. For improved translation of evidence for or against the use of cryotherapy in sport, it is suggested that future study design and methodologies should reflect contemporary demands within sporting environments where cryotherapy protocols for injury, rehabilitation or recovery are a feature of athlete management through investigation of individual response, and multi-measures of wellbeing and performance.